A novel strategy for eradication of staphylococcal biofilms using blood clots - Grooters, Kayla E.; Hayes, Sheridan L.; Richter, David M.; Ku, Jennifer C.; Sawyer, Robert; Li, Yong (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionInfections with coagulase negative staphylococcal species (CoNS) are a major cause of mortality and morbidity in joint and heart valve replacement procedures, largely due to biofilm formation. Cells within biofilms have higher rates of antibiotic resistance than their planktonic counterparts; consequently, novel mechanisms are needed to combat these infections.MethodsTo enhance antibiotic delivery and penetration, this innovative study involved treating CoNS biofilms with murine blood clots impregnated with antibiotics. We then investigated the impact of this treatment on biofilm density, metabolism, and architecture.ResultsOur pilot study demonstrates that this method of antibiotic delivery results in improved biofilm clearance, relative to conventional exposure methods.DiscussionOur results demonstrate that blood clot exposure has an intrinsic impact on biofilm density and potentially reduces colonization, warrenting further investigation into the mechanism.